PENINGKATAN HASIL BELAJAR KIMIA SISWA SMAN 4 MUARO JAMBI DENGAN MEDIA BERVARIASI - ELIA ROSITA (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2023)
This research was conducted on class XI.Mia.1 students at SMA Negeri 4 Muaro Jambi in the odd semester of the 2022/2023 academic year with a total of 30 students. The actions were carried out in 3 cycles, namely cycle I, cycle II and cycle II regarding KD 3.11 and 4.11 using varied media. The research data is in the form of a learning process which includes observations of activeness, attention, discipline and assignments/recitations and the results of evaluation of student learning which are collected using learning achievement tests. The results showed that there was an increase in students' understanding of the material for hydrocarbon compounds from the first cycle was moderate (35%) to good (74%) in cycle II and very good (91%) in cycle III. Likewise in the results of the learning evaluation, namely the post tests in cycle I, cycle II and cycle III experienced an increase from the average post test in cycle I which was 76.97 with 35% completeness while in cycle II the class average value was 81.41 with completeness 74% and 85.26 with 91% completeness in cycle III. ABSTRAKPenelitian ini dilakukan pada Siswa kelas XI.Mia.1 SMA Negeri 4 Muaro Jambi semester ganjil Tahun Pelajaran 2022/2023 dengan jumlah siswa 30 orang. Tindakan dilakukan dalam 3, siklus, yaitu siklus I , siklus II dan siklus II tentang KD 3.11 dan 4.11 Menggunakan media bervariasi. Data hasil penelitian berupa proses pembelajaran yang meliputi pengamatan terhadap keaktifan, perhatian, kedisiplinan dan penugasan/ resitasi dan hasil evaluasi pembelajaran siswa yang dikumpulkan dengan menggunakan tes hasil belajar. Hasil penelitian menunjukkan terjadi peningkatan pemahaman siswa terhadap materi senyawa hidrokarbon dari siklus I cukup (35%) menjadibaik (74%) pada siklus II dan sangat baik ( 91 %) pada siklus III . Demikian juga pada hasil evaluasi belajar yaitu post tes pada siklus I, siklus II dan siklus III megalami kenaikan dari rata-rata post tes pada siklus I adalah 76,97 dengan ketuntasan 35% sedangkan pada siklus II nilai rata-rata kelas 81,41dengan ketuntasan 74% serta 85,26 dengan ketuntasan 91 % pada siklus III.